2019
DOI: 10.3390/ph12040186
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Saccharide-Based Aliphatic and Aromatic Esters as Antimicrobial and Antibiofilm Agents

Abstract: A small library of sugar-based (i.e., glucose, mannose and lactose) monoesters containing hydrophobic aliphatic or aromatic tails were synthesized and tested. The antimicrobial activity of the compounds against a target panel of Gram-positive, Gram-negative and fungi was assessed. Based on this preliminary screening, the antibiofilm activity of the most promising molecules was evaluated at different development times of selected food-borne pathogens (E. coli, L. monocytogenes, S. aureus, S. enteritidis). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…Morin et al [67] and Siena et al [68] reported that, a variety of modified FAs are promising molecules in the treatment of cancers. Also, there were several studies dealing with anticancer, antimicrobial and anti-inflammatory activities of SE derivatives [69, 70]. Our results correlated with those reported by An and Feng [71], whose evaluated the antitumor activity of series of glucosyl esters derivatives against three cancer cells, human breast adenocarcinoma (MCF-7), human colon carcinoma (K562) and human hepatoma (HepG2).…”
Section: Resultssupporting
confidence: 88%
“…Morin et al [67] and Siena et al [68] reported that, a variety of modified FAs are promising molecules in the treatment of cancers. Also, there were several studies dealing with anticancer, antimicrobial and anti-inflammatory activities of SE derivatives [69, 70]. Our results correlated with those reported by An and Feng [71], whose evaluated the antitumor activity of series of glucosyl esters derivatives against three cancer cells, human breast adenocarcinoma (MCF-7), human colon carcinoma (K562) and human hepatoma (HepG2).…”
Section: Resultssupporting
confidence: 88%
“…The purification of the residue was done by column chromatography (cyclohexane/ethyl acetate 6:4) and gave 6-O-monolauroyl-glucose as a white solid. (0.163 g, Yield: 80%) [28]. 1 Triethylamine (18.3 mL, 130.9 mmol) was added to a stirred suspension of trehalose 1 (1.12 g, 3.27 mmol) in dichloromethane (15 mL).…”
Section: Synthesis Of Glucose Monolauratementioning
confidence: 99%
“…The antimicrobial activities of sugar fatty acid esters produced by lipase-catalyzed synthesis and of chemically synthesized aromatic lactose esters have also been tested. The highest inhibition for Escherichia coli, Listeria monocytogenes, Staphylococcus aureus and Salmonella enteritidis was exhibited by mannose C10 ester and lactose biphenylacetate [19]. The antioxidant properties of sugar cane juice phenolic extracts of cinnamic, caffeic and sinapic acid were demonstrated by inhibition of spontaneous peroxidation of rat brain homogenates, suggesting the potential of such compounds for oxidative stress therapy [20].…”
Section: Introductionmentioning
confidence: 99%